Facile synthesis of porous organic polymers bifunctionalized with azo and porphyrin groups. Issue 119 (17th November 2015) - Jiang, Xiaowei; Liu, Yunfei; Liu, Jun; Luo, Yali; Lyu, Yinong
Abstract : Azo and porphyrin bifunctionalized porous polymer networks (azo-PPors) with BET surface areas up to 750 m 2 g −1 were synthesized via a catalyst-free direct coupling of tetra(4-nitrophenyl)porphyrin and aryl amine monomers. Abstract : Azo and porphyrin bifunctionalized porous polymers networks (azo-PPors) were synthesized via a catalyst-free direct coupling of tetra(4-nitrophenyl)porphyrin and several readily available aryl amine monomers. The resulting porous solids exhibited surface areas up to 750 m 2 g −1, with high thermal and chemical stability. Owing to the high concentration of Lewis basic N-sites at their surfaces (derived from porphyrin rings and azo units), these azo-PPors have high CO2 capture (up to 2.45 mmol g −1 ) and good selectivity for CO2 /CH4 adsorption (5) at 273 K/1.0 bar, thus showing good potential for CO2 capture.